RELIGION, CULTURAL TRANSFORMATION, AND MODERNIZATION: A Narrative on the Shift of Religious Paradigm of the Community in Surakarta - Lilam, Lilam Kadari Nuriyanto; Mibtadin, Mibtadin; Arnis, Arnis Rachmadhani (The Sunan Ampel Review of Political and Social Sciences, 2022)
Globalization is characterized by advances in science and technology that are inevitable by the community, including the people of Surakarta. People in Surakarta are in dilemma between tradition and modernization. Education, transportation, and economic advancement have transformed the social, religious, and cultural aspects of the people in Surakarta over the last three decades. Thus, how is the narrative of the paradigm shift of religiosity of the Surakarta community amid modernization? This descriptive qualitative study collected data through observation, in-depth interviews, and documentation. The analysis employed an interactive analysis model. The findings revealed that the paradigm shift of religiosity of the Surakarta community is directly proportional to the social, political, economic, and cultural changes. There is a shift in the religious perspective of the Surakarta community known as hijrah from the abangan Muslim community to Islamist activism or new santri with all the limitations of understanding and Islamic doctrine, which requires assistance in terms of Javanese Islamic culture and local beliefs to avoid uprooting them. As a result of hijrah and becoming Islamic activism, people left the Javanese culture such as Kejawen and local beliefs. However, some of them have transformed the culture to fit the teachings of Islam. So far, those who hijrah to NU still adhere to religious traditions and even transform Javanese culture to suit the times. Meanwhile, Islamic activism has left Javanese Islamic traditions and local beliefs. The shift in religious paradigm asserts two things. They are internal and external encouragement. First, internal factors are in the form of encouragement from within religious communities. Second, external factors are external stimuli that can encourage a shift in the Surakarta community's religious perspective.